2021
DOI: 10.1007/s11191-021-00317-9
|View full text |Cite
|
Sign up to set email alerts
|

Critical Rationalism and Trust in Science

Abstract: In this paper, I consider whether the critical rationalist philosophy of science may provide a rationale for trusting scientific knowledge. In the first part, I refer to several insights of Karl Popper’s social and political philosophy in order to see whether they may be of help in offsetting the distrust of science spawned by the COVID-19 pandemic. In the second part, I address the more general issue of whether the theoretical principles of the critical rationalist philosophy of science may afford a foundatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…There is no denying that truth is an elusive concept. Yet, despite the many existing, question-begging, and justifiably criticized definitions, there is a way to make sense of truth by conceiving it as an outcome of a socially established cognitive regime capable of producing reliable and adequate knowledge of the natural and social world (Chmielewski, 2022(Chmielewski, , p. 1687). The problem with today's democracy is that it operates as if such knowledge were no longer relevant.…”
Section: Discussionmentioning
confidence: 99%
“…There is no denying that truth is an elusive concept. Yet, despite the many existing, question-begging, and justifiably criticized definitions, there is a way to make sense of truth by conceiving it as an outcome of a socially established cognitive regime capable of producing reliable and adequate knowledge of the natural and social world (Chmielewski, 2022(Chmielewski, , p. 1687). The problem with today's democracy is that it operates as if such knowledge were no longer relevant.…”
Section: Discussionmentioning
confidence: 99%
“…In supporting the introduction of a 4th phase, seeking to bridge the "classroom-society" divide, interviewees indicated that this needed careful attention. All interviewees recog-nised the need for science education to address "the future we want" [23] and, in so doing, accepted there was a potential need to go beyond the 3-stage model and, hence, agreed with the need, as expressed in the literature, to prepare a collective body of citizens who are actively [9], scientifically [10] and collectively [4] able to participate in resolving encountered societal concerns.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, second, there seemed to be a lack of ability, at both individual and collective levels, to reconcile such a science-influenced society dilemma [7,8]. This could be seen as raising the question as to whether promoting conceptually science-informed individuals is sufficient, or whether there is a further need to embrace a wider vision of science education, such as preparing a collective body of citizens who actively [9], scientifically [10] and collectively [4] participate in resolving encountered societal concerns.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that classical rationalism is associated with the deductive method of cognition, when knowledge about the world can be obtained only with the "pure mind", its undoubted "innate" ideas and strictly logical reasoning that are not based on experience. It means forwarding 1499 bold theories and a constant lack of trust in them [22]. The rejection of empirical data was justified by the fact that the undoubted "innate" ideas of the pure mind are the most general truths from which less general truths can be derived by deduction.…”
Section: The Comprehensive Theoretical Basis 21 Rationalism and Empir...mentioning
confidence: 99%